Occasion-sensitivity selected essays - Travis, Charles, 1943- (Oxford : Oxford University Press, 2008)
Charles Travis presents a series of essays in which he has developed his distinctive view of the relation of thought to language. He argues that there are varying conditions of correctness which determine whether words express a given concept, and thus that meaning does not determine truth conditions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Semantics (Philosophy); Language and languages -- Philosophy; Context (Linguistics); Truth; Meaning (Philosophy)